Prevalence and Risk Factors of High Blood Pressure among Elderly People - Parajuli, Keshab; Sharma, Mahendra Prasad; Ghimire, Raju; Karki, Kshitij (Journal of Nepal Health Research Council, 2025)
Background: High Blood Pressure, a prevalent condition exacerbated by population growth, disproportionately affects the elderly, with over two-thirds of individuals aged 65 and above affected. This study aimed to evaluate the prevalence and risk factors of high blood pressure among elderly residents of Chandragiri Municipality in Kathmandu. Methodology: A cross-sectional was applied, and the respondents were selected from randomly chosen wards of Chandragiri Municipality. Elderly individuals aged over 60 years residing in the area, regardless of permanency, were included. Data analysis was conducted using SPSS software, with the Chi-square test employed to assess associations between high blood pressure and various risk factors at a significance level of 5%. Results: The study included 418 individuals, of whom 48.8% were currently suffering from high blood pressure. The majority was male 55.5% and married 73.7%, with Chhetri 45.2% and Brahmin 40.7% being the most prevalent ethnic groups. Most respondents were illiterate 44.3% and resided in joint families 68.4%. Reported risk factors for high blood pressure included tobacco smoking 37.3%, alcohol consumption 36.1%, and non-vegetarian diets 85.9%. Conclusion: Significant relationships were observed between blood pressure and age, sex, marital status, tobacco smoking, and alcohol consumption. Conversely, religion, ethnicity, education level, family type, BMI, diet type, and physical activity did not exhibit noteworthy associations with high blood pressure in this sample. These findings underscore the multifactorial nature of high blood pressure and its diverse risk factors. Keywords: Elderly people; high blood pressure; prevalence; Risk factors.